Singularly Perturbed Equations with Impulse Action - Kaplun, Yu. I.; Samoilenko, A. M.; Samoilenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We propose and justify an algorithm for the construction of asymptotic solutions of singularly perturbed differential equations with impulse action.